Green trust as a mediator in the influence of functional, social, and emotional values on eco-friendly product purchases at Fore Coffee in Padang - Pratama, Muhammad Fauzan; Engriani, Yunita (Marketing Management Studies, 2024)
This research aims to analyze the influence of Functional value , Social value and Emotional Value on Purchase Decisions Mediated by Green Trust on Environmentally Friendly Products at Fore Coffee Stores in Padang City. The population in this research are all people who live in the city of Padang and have bought or know about Fore Coffee products. This research involved 251 respondents as samples. Data collection was carried out by distributing online questionnaires, and data was processed using SmartPLS software. The findings of this research show that (1) Functional value has a significant positive effect on Purchase Decision. (2) Functional value has a significant positive effect on Green Trust. (3) Social value has a positive effect on Purchase Decision. (4) Social value has a significant positive effect on Green Trust. (5) Emotional has a significant positive effect on Purchase Decision. (6) Emotional Value has a significant positive effect on Green Trust. (7) Green Trust has a significant positive effect on Purchase Decision. (8) Emotional Value has a positive effect on Purchase Decisions through Green Trust as mediation. (9) Functional value has a positive and significant effect on Purchase Decisions through Green Trust as mediation. (10) Social value has a positive influence on Purchase Decisions through Green Trust as mediation.